Sensitivity Analysis of Power Regulation Parameters for Doubly-Fed Pumped Storage Units - SUN Maoxiang; WANG Liying; WANG Dakai; FAN Honggang; ZHANG Jiajie; WANG Zeyang (Renmin Zhujiang)
This paper aims to investigate the impact of power regulation controller parameters on the system's control performance of doubly-fed pumped storage units.Based on the power regulation control strategy,the paper employs an orthogonal experimental design to analyze the sensitivity of power regulation controller parameters.Four parameters in the power regulation controller (each parameter selected at 4 different levels) are subjected to orthogonal design.Integral of time-weighted absolute error (ITAE) is chosen as the optimization objective.Stable operating conditions are identified through range analysis.The sensitivity of parameters is quantified by range analysis to distinguish the major and minor parameters affecting the control performance of the system.The computational results demonstrate that a smaller ITAE value indicates higher dynamic response quality of the system,smaller errors,and faster convergence speed.The proportional coefficient of the current regulation module significantly influences the control performance of the system.However,the integral coefficient of the power regulation module,the integral coefficient of the current regulation module,and the proportional coefficient of the current regulation module have a relatively minor effect.The sensitivity analysis of power regulation controller parameters provides a theoretical foundation for the reliable operation of doubly-fed pumped storage units in the power system.